Mastery of teletherapy is related to better therapeutic relationship and presence in teletherapy: the development of the teletherapy intervention scale - Békés, Vera; Aafjes-van Doorn, Katie; Luo, Xiaochen; Balarajan, Sanjeev; Hopwood, Christopher J. (Frontiers in Psychology, 2023)
Providing teletherapy requires a unique therapeutic approach and mastery of the teletherapy context. We aimed to develop a self-report scale for therapeutic interventions pertinent to teletherapy, and to examine its relationship with teletherapy process variables, and therapists' attitudes towards teletherapy technology.A total of 839 therapists participated in a survey study that included standardized measures of therapeutic process (real relationship, working alliance, therapeutic presence), attitudes towards and intention to use teletherapy in the future, and a list of 13 teletherapy intervention items that we hypothesized to be specific to the teletherapy format.Results. Twelve of the 13 teletherapy intervention items loaded on one factor, with good reliability. The 12-item Teletherapy Intervention Scale was positively related to working alliance, the real relationship, therapeutic presence in teletherapy sessions, as well as to positive attitudes towards teletherapy and intention to use teletherapy in the future.Discussion. Aspects specific to the practice of teletherapy may be successfully captured by a self-report scale, and adequately navigating the challenges and opportunities of teletherapy might enhance the therapeutic process. Further studies are needed to provide additional validation of the scale, and in how to best use this Teletherapy Intervention Scale in research and clinical training.